2017
DOI: 10.1016/j.conctc.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Searching for cures: Inner-city and rural patients' awareness and perceptions of cancer clinical trials

Abstract: Fewer than 5% of cancer patients participate in clinical trials, making it challenging to test new therapies or interventions for cancer. Even within that small number, patients living in inner-city and rural areas are underrepresented in clinical trials. This study explores cancer patients' awareness and perceptions of cancer clinical trials, as well as their perceptions of patient-provider interactions related to discussing cancer clinical trials in order to improve accrual in cancer clinical trials. Intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 46 publications
3
32
0
Order By: Relevance
“…Free text comments from the survey revolved around the idea of the BAME community being used as 'guinea pigs' for trials to verify vaccine results, and mistrust around government strategies. Similar sentiments have been found in US studies [17], [20], [21]. This was likely to have taken in uence from social media views at the time of survey completion, particularly those highlighting adverse events from vaccine trials and vaccines trials being rushed.…”
Section: Discussionsupporting
confidence: 68%
“…Free text comments from the survey revolved around the idea of the BAME community being used as 'guinea pigs' for trials to verify vaccine results, and mistrust around government strategies. Similar sentiments have been found in US studies [17], [20], [21]. This was likely to have taken in uence from social media views at the time of survey completion, particularly those highlighting adverse events from vaccine trials and vaccines trials being rushed.…”
Section: Discussionsupporting
confidence: 68%
“…One international effort, supported by the United States Agency for International Development (USAID) and others, developed a handbook for clinical trial communications, an example containing tools that complement the CTTI recommendations [33]. A recent study on the effectiveness of communications among inner city and rural populations for cancer trials found that television advertising was influential [34]. These activities are encouraging, and our recruitment recommendations support the need to extend recruitment communications across more domains.…”
Section: Discussionmentioning
confidence: 79%
“…Rural patients are less likely to seek information about research participation than are urban patients 31 and are more likely to possess negative views about medical research. 39 Community-based interventions to increase awareness about research opportunities and the value of clinical trial could provide a valuable pathway to alleviating rural disparities in cancer care and outcomes. [40][41][42] Rural Lymphoma Patient Priorities…”
Section: Discussionmentioning
confidence: 99%